Fauna in Šiauliai Manor in the 17th–18th Centuries according to Zooarchaeological and Historical Data - Jonauskienė, Viktorija; Ostašenkovienė, Virginija (Acta humanitarica academiae Saulensis, 2024)
Since 1589, Šiauliai became the center of Šiauliai Crown Estate, which maintained the ruler’s estate. From the 17th century onwards, Šiauliai Crown Estate was constantly entrusted to manage by loans to nobles of the Grand Dutchy of Lithuania, with its administrators changing over time (from 1678 to 1696, it belonged to King John III Sobieski). Šiauliai Crown Estate was administered by their appointed administration: an economist, vice-economist, and local officials. Officials of the manor administration were assisted by provision clerks, scribes, and other staff. The residence of the administration became Šiauliai Manor.The first small-scale archaeological investigations in the residential estate of Šiauliai Manor were carried out in 1997 (led by Audronė Šapaitė). More extensive archaeological excavations were conducted at the manor between 2010 and 2022. During this period, a total area of 533 square meters was excavated, and 10,577 square meters were surveyed. The remains of 11 structures dating from the 17th century to the early 20th century were localized within the territory of Šiauliai Manor, and 8,286 archaeological artifacts were collected along with abundant zooarchaeological material.In total, 1,114 fragments of zooarchaeological material dating from the 17th to the 18th centuries were collected and analyzed from archaeological cultural layers of the manor. The studied material provides an overview of the distribution of domestic (85 %) and wild (15 %) fauna in the zooarchaeological material of Šiauliai Manor. The surviving material allows insights into prevailing trends such as differences in the quantities of domestic and wild fauna, and to some extent, the presence of domestic animals in the manor, as well as the consumption of luxury goods and reflections of Western culture in Šiauliai Manor. The inventories of Šiauliai economy and the obtained statistical analysis provide an opportunity to gain a more comprehensive understanding of the daily life of the ruler’s table in Šiauliai Manor during the 17th–18th centuries and to extract the maximum information from the available/remaining data.
Keywords: Šiauliai Manor; Šiauliai Crown Estate; inventories; zooarchaeology; domestic fauna; wild fauna; hunting